2015
DOI: 10.3109/21695717.2014.994869
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of age related hearing loss

Abstract: Presbycusis or age related hearing loss (ARHL) is the most common sensory deficit in the elderly. It is a multifactorial condition that involves a multitude of intrinsic and extrinsic factors acting on the inner ear over a lifetime, which cumulatively lead to impairments in cochlear transduction of acoustic signals. ARHL is characterized by a loss of hearing sensitivity and a decreased ability to understand speech in the presence of background noise. Epidemiological studies have shown that in the USA hearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
0
22
0
5
Order By: Relevance
“…Diese sensorineurale symmetrische Altersschwerhörigkeit ist deutlich im Hochtonfrequenzbereich ausgeprägt [5,12]. Die altersbedingte Hörminderung kann entweder auf lebenslange exogene und endogene Einflüsse sowie auf genetische Faktoren zurückzuführen sein [7,13,14]. Die Lärmexposition (Intensität und Dauer des Lärms) tritt in der Literatur als prädisponierender exogener Risikofaktor auf [5].…”
Section: Hintergrundunclassified
See 1 more Smart Citation
“…Diese sensorineurale symmetrische Altersschwerhörigkeit ist deutlich im Hochtonfrequenzbereich ausgeprägt [5,12]. Die altersbedingte Hörminderung kann entweder auf lebenslange exogene und endogene Einflüsse sowie auf genetische Faktoren zurückzuführen sein [7,13,14]. Die Lärmexposition (Intensität und Dauer des Lärms) tritt in der Literatur als prädisponierender exogener Risikofaktor auf [5].…”
Section: Hintergrundunclassified
“…Die Lärmexposition (Intensität und Dauer des Lärms) tritt in der Literatur als prädisponierender exogener Risikofaktor auf [5]. Zu den negativen Einflüssen zählen zudem Ototoxine (ohrschädigende Substanzen), Rauchen [12], Infektionen, Schlaganfall [6,14], Hypertonie, Herz-Kreislauf-Erkrankungen, Diabetes und Durchblutungsstörungen [7,13]. Das Potenzial der Komorbiditäten als Risikofaktoren für Altersschwerhö-rigkeit wird in der Forschung kontrovers diskutiert.…”
Section: Hintergrundunclassified
“…Hearing loss (HL) is the most prevalent sensory impairment in both childhood and adulthood 1, 2 . According to the last update of the World Health Organization (WHO), approximately 360 million people worldwide, equaling 5% of the world’s population, suffer from a disabling HL (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The second reason this finding is critical is that it highlights that the brain remains plastic in older adults and is susceptible to be modified based on experiences. In the current context this is critical, as hearing difficulties in older adults are nearly universal (Gates & Mills, 2005;Quaranta et al, 2015), and one of the most commonly reported hearing difficulty is understanding speech in noisy environments.…”
Section: Discussionmentioning
confidence: 99%